(untitled) (Journal of Engineering, 2015)
The present research aims to study the effect of friction stir welding (FSW) parameters on temperature distribution and tensile strength of aluminum 6061-T6. Rotational and traverse speeds used were (500,1000,1400 rpm) and (14,40,112 mm/min) respectively. Results of mechanical tests showed that using 500rpm and 14mm/min speed give the best strength. A three- dimensional fully coupled thermal-stress finite element model via ANSYS software has been developed. The Rate dependent Johnson-Cook relation was utilized for elasto-plastic work deformations. Heat-transfer is formulated using a moving heat source, and later used the transient temperature outputs from the thermal analysis to determine equivalent stresses in the welded plates via a 3-D thermo- mechanical simulation. Motion due to rotation and translation of the tool induces asymmetry in the material flow and heating across the tool pin. The rotation speed results in stirring and mingling of material around the tool and the movable tool moves the stirred material from the front to the back of the tool and finishes welding process. Higher rotation speed rates create higher temperature because of higher friction heating and result in more powerful stirring and mingling of material. A good agreement is evident between experimental and Ansys results.